Human Behavior and the Social Environment II - Payne, Whitney; Open Textbook Library (Open Textbook Library, 2020)
These materials will help students and instructors alike explore human behavior and how it is shaped and impacted by both traditional and non-traditional paradigms. This text will also support the reader in having a deeper understanding of how the environment, in all of its complexity, can affect individuals, families, groups, and communities. It is my hope that the information contained in this book will help you, as a future social worker, approach client systems with empathy, understanding, and a compassionate curiosity that allows for comprehensive assessment, individualized approaches to treatment, and continuity of care.
I. Traditional Paradigms & Dominant Perspectives on Individuals -- II. Alternative Perspectives on Individuals -- III. Perspectives on Families -- IV. Perspectives on Groups -- V. Stages of Group Development & Group Think -- VI. Perspectives on Organizations -- VII. Perspectives on Communities -- VIII. Communities & Police Relations -- IX. Global Perspectives & Theories -- X. Additional Resources
In English.
Description based on online resource
Keywords: Psychology -- Textbooks